CLINICAL CLUES FOR DIAGNOSIS IN PAINFUL OPHTHALMOPLEGIA - Baran SINIR; Özge ÖCEK; Berfin Kardelen Aydın; Pınar ORTAN (Eskisehir Medical Journal, Eskisehir City Hospital, 2026)
Introduction: Painful ophthalmoplegia (PO) is a heterogeneous clinical syndrome that may present with periorbital or hemicranial headache accompanied by ophthalmoplegia, diplopia, ptosis, Horner syndrome, and facial hypoesthesia. Because its etiology encompasses a wide range of vascular, inflammatory, infectious, neoplastic, metabolic, orbital, and cryptogenic causes, the differential diagnosis can be challenging. This study aimed to evaluate clinical and examination findings that may help guide the diagnostic work-up in patients presenting with PO. Methods: Patients hospitalized with a diagnosis of PO between 2012 and 2023 were retrospectively reviewed. Demographic data, clinical features, patterns of cranial nerve and extraocular muscle involvement, and imaging and laboratory findings were recorded. Cases were classified according to etiological and presumed anatomical characteristics. Results: Among 34 patients (mean age, 53.2 ± 17.7 years; 52.9% male), the most common etiology was diabetic cranial neuropathy (29.4%), followed by orbital myositis (17.6%), probable Tolosa-Hunt syndrome (8.8%), and intracranial aneurysm (8.8%). Isolated abducens nerve palsy was observed in 13 patients (38.2%), isolated oculomotor nerve palsy in eight (23.5%), and multiple cranial nerve involvement in six (17.6%). Seven patients (20.6%) had ophthalmoplegia secondary to extraocular muscle involvement, mainly orbital myositis and thyroid ophthalmopathy. Conclusion: Painful ophthalmoplegia is a clinical syndrome with a broad etiological spectrum that warrants urgent exclusion of potentially life-threatening causes. A localization-based clinical assessment may help prioritize the differential diagnosis and guide targeted imaging and laboratory investigations, facilitating timely initiation of appropriate treatment